DETERMINATION OF THE OPTIMUM OPERATING CONDITIONS IN THE GRANULATION OF GAMMA ALUMINA CATALYST SUPPORT - Dhari Jawad, Alaa; Richeh, Ibrahim; Saleh, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
Granulation Technique for Gamma Alumina Catalyst Support was employed in inclined disk granulator (IDG), rotary drum granulator (RD) and extrusion – spheronization equipments .Product with wide size range can be produced with only few parameters like rpm of equipment, ratio of binder and angle of inclination. The investigation was conducted for determination the optimum operating conditions in the three above different granulation equipments.Results reveal that the optimum operating conditions to get maximum granulation occurred at ( speed: 31rpm , Inclination:420 , binder ratio:225,300% ) for the IDG,( speed: 68rpm , Inclination: 12.50 , binder ratio: 300% ) for the RD and ( speed:1200rpm , time of rotation: 1-2min )for the Caleva spheronizer used in the extrusion spheronization method. These results are compatible with similar works on granulation of different materials [1, 2, and 3].